THE WAYS OF IMPROVING SPEAKING ABILITY IN ENGLISH (Conference Zone, 2022)
This article is about ways of improving the ability of speaking in English and the students’ perspective on it. There are several different kinds of methods which can be fruitful in developing students’ oral skills. Most essential methods are discussed in this article